Cultivating critical thinking: the development and impact of PBL worksheets in elementary science learning - Tri Damayanti; Herpratiwi; Fatkhur Rohman; Nurhanurawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study was motivated by the low level of critical thinking skills among primary school students in science learning, which requires innovation in teaching materials. The purpose of this study was to develop and test the effectiveness of Student Worksheets based on Problem-Based Learning (PBL) to improve critical thinking skills in the subject of 'Light and Its Properties'. Research and Development (R&D) were conducted using the ADDIE model and a quasi-experimental design. The research subjects consisted of 52 fifth-grade elementary school students, divided into experimental and control groups. The research instruments included essay tests, observation sheets, and assessment rubrics. Expert validation results showed that the Student Worksheet was deemed highly valid in terms of media (4.58), valid in terms of material (4.44), and valid in terms of language (4.46). The effectiveness test results proved that the experimental class experienced a significant increase in all critical thinking indicators (total score of 20.9) compared to the control class (14.1). Statistical tests (p < 0.001) and effect sizes (Cohen's d = 1.65-2.45) confirmed that this improvement was statistically significant and had a large effect. It was concluded that PBL-based Student Worksheets were effective in fostering critical thinking skills in primary school students and were recommended for use in science learning.